THE INFLUENCE OF BOUNDARY LAYERS ON HEAT TRANSFER AROUND PLANE AND SHAPED SURFACES - BRODNIANSKÁ, Zuzana; KONIAR, Ján (Trends in education, 2011)
The present contribution described the influence of boundary layers on heat transfer, forming around plane and shaped surfaces in forced convection. Students are informed about heat transfer processes in various energetic equipments in the Environmental Technology study programme, in subjects Process Mechanical Engineering, Energetic Machines and Equipment and Energetic Changes. Design of experimental model, that can be utilized as a didactic tool in educational process, for study of heat transfer processes, is present in the contribution.
Keywords: heat transfer; boundary layer; shaped surface.